Crossing Spatial and Temporal Boundaries in Globally Distributed Projects: A Relational Model of Coordination Delay - Cummings, Jonathon N; Espinosa, J. Alberto; Pickering, Cynthia K (Information systems research, 2009)
In globally distributed projects, members have to deal with spatial boundaries (different cities) and temporal boundaries (different work hours) because other members are often in cities within and across time zones. For pairs of members with spatial boundaries and no temporal boundaries (those in different cities with overlapping work hours), synchronous communication technologies such as the telephone, instant messaging (IM), and Web conferencing provide a means for real-time interaction. However, for pairs of members with spatial and temporal boundaries (those in different cities with nonoverlapping work hours), asynchronous communication technologies, such as e-mail, provide a way to interact intermittently. Using survey data from 675 project members (representing 5,674 pairs of members) across 108 projects in a multinational semiconductor firm, we develop and empirically test a relational model of coordination delay. In our model, the likelihood of delay for pairs of members is a function of the spatial and temporal boundaries that separate them, as well as the communication technologies they use to coordinate their work. As expected, greater use of synchronous web conferencing reduces coordination delay for pairs of members in different cities with overlapping work hours relative to pairs of members with nonoverlapping work hours. Unexpectedly, greater use of asynchronous e-mail does not reduce coordination delay for pairs of members in different cities with nonoverlapping work hours, but rather reduces coordination delay for those with overlapping work hours. We discuss the implications of our findings that temporal boundaries are more difficult to cross with communication technologies than spatial boundaries.